The Role of the Jamik Kauman Mosque in Regency Society Sragen, Central Java - Aqshal Hafizh Sukamto, Resultan (Jurnal Multidisiplin Indonesia, 2023)
The Jamik Kauman Mosque is one of the oldest mosques in Sragen Regency, Central Java, which plays a major role in the development of Islamic education. The Jamik Kauman Mosque is one of the oldest mosques in Sragen Regency, Central Java, which was built by representatives of the Surakarta Kasunanan Palace and is able to attract the attention of the public with its various programs and activities. This research aims to describe the role of the Jamik Kauman Mosque in society in Sragen Regency, Central Java. This research method is a descriptive qualitative approach with data collection techniques in the form of interviews, observation and document study. The research subjects were the congregation of the Jamik Kauman Mosque in Sragen. Sampling used a purposive sampling technique, namely using criteria according to research needs. Data analysis uses the Miles and Huberman interactive model which consists of data reduction activities, data presentation, and drawing conclusions. The research results found that the role of the Jamik Kauman Mosque in society can be seen from the function it carries out. In religious functions, mosques act as places of worship such as five daily prayers and other religious activities. In terms of social functions, mosques act as a means of gathering for residents. In terms of economic function, the mosque acts as an intermediary in distributing aid through the LAZIS NU cooperative. In terms of educational function, mosques act as non-formal educational institutions. In its missionary function, the mosque acts as a means of preaching through holding large recitation activities and regular lectures.